Biogeochemical cycling of cadmium isotopes along a high-resolution section through the North Atlantic Ocean. (1st January 2015) - Conway, Tim M.; John, Seth G.
Abstract: Cadmium (Cd) is a bioactive trace element in the oceans, with a nutrient-like distribution that closely matches dissolved phosphate. Seawater-dissolved stable Cd isotope ratios (δ 114 Cd) are a relatively new parameter, which show much promise for furthering our understanding of the biogeochemical cycling of Cd in the oceans. Here we present a high-resolution paired section of dissolved Cd concentrations and dissolved δ 114 Cd from 21 open-ocean stations along the US GEOTRACES GA03 transect through the North Atlantic Ocean. Dissolved Cd concentrations along the section are strongly influenced by water-mass distribution and the cycling of Cd. The highest dissolved Cd concentrations (400–540 pmol kg −1 ) are associated with Antarctic-sourced water masses, whilst biological uptake in the surface ocean results in a strong vertical gradient in dissolved Cd towards the surface, reaching as low as 0.03 pmol kg −1 in western surface waters. Dissolved δ 114 Cd is also characterized by a vertical gradient from ∼+0.2‰ in the deep ocean to +2‰ to +5‰ in the Cd-depleted surface ocean (relative to NIST SRM 3108). This variability in δ 114 Cd can be ascribed to mixing of Antarctic and North Atlantic water masses, together with fractionation due to in situ biological uptake of light Cd in the very surface ocean. Subtle deviations from this overall pattern of dissolved Cd concentration and dissolved δ 114 Cd are observed within low-oxygen waters off North Africa, where a dissolved Cd deficit relative to phosphate is associated with higher dissolved δ 114 Cd values. Together with elevated particulate Cd and Ba, this suggests that Cd sulfide precipitation is occurring within the water column of the North Atlantic, constituting a potentially important sink for isotopically light Cd. Additionally, the first measurements of dissolved δ 114 Cd within a hydrothermal plume at the Mid-Atlantic Ridge show that Cd is scavenged from the dissolved phase, leaving the remnant dissolved Cd isotopically heavier. Constraining the significance of these marine sinks for dissolved Cd is important, not only for our understanding of the marine biogeochemical cycling of Cd in the modern oceans, but also for the successful application of the microfossil Cd/Ca proxy and the development of δ 114 Cd as a tracer for past-ocean biogeochemical cycling.